The correlation between subordinate fish eye colour and received attacks: a negative social feedback mechanism for the reduction of aggression during the formation of dominance hierarchies - Miyai, Caio A. [UNESP]; Sanches, Fabio H. Carretero [UNESP]; Costa, Tânia Marcia [UNESP]; Colpo, Karine Delevati [UNESP]; Volpato, Gilson Luiz [UNESP]; Barreto, Rodrigo E. [UNESP] (Elsevier Gmbh, Urban & Fischer Verlag, 2011)
Eye darkening has been linked to social status in fish. The subordinate's eyes darken, while the eyes of the dominant fish become pale. Although this phenomenon has been described in salmonid fishes and in the African cichlid Nile tilapia Oreochromis niloticus, it is unclear whether eye darkening correlates with a reduction in aggressive behaviour. Thus, we evaluated the link between social status and eye darkening. We evaluated whether the eye colours of subordinate fish correlate with the frequency of received attacks in a neotropical fish, the pearl cichlid Geophagus brasiliensis. We paired pearl cichlids and quantified both the aggressive behaviour and the eye darkening of each fish. As has been described for Nile tilapia and Atlantic salmon, a clear-cut hierarchical relationship formed, where dominance and subordination were associated with pale and dark eye colours, respectively. Initially, eye colour darkening was positively correlated with the frequency of received attacks; however, a negative association occurred following eye darkening, in which the intensity of aggressive interactions decreased. Thus, fish that initially received a high number of attacks signalled subordination more rapidly and intensely (rapid and dramatic eye darkening), thereby inducing a negative social feedback mechanism that led to reduced aggression. (C) 2011 Elsevier GmbH. All rights reserved.
Keywords: Cichlidae; Geophagus brasiliensis; Agonistic behaviour; Eye colour darkening; Social hierarchy